VD_FINDINFO ML / 2023 / 181 vom 8. Dezember 2023 - VD Tribunal cantonal (2023)
CONTRÔLE SPÉCIAL, AVANCE DE FRAIS, POURSUITE EN PRESTATION DE SÛRETÉS | 697hbis CO, 38 al. 1 LP, 43 ch. 3 LP, 80 al. 1 LP